Efeitos do chá mate (llex paraguariensis) na estrutura óssea de ratas na perimenopausa - Pereira, Camila Scacco [UNESP] (2015)
Perimenopause is a period marked by a reduction in areal bone mineral density (aBMD) associated with increased oxidative stress, and natural antioxidants have been used as an alternative to reverse this situation. In this context, the present study was to investigate the effects of mate tea (MT) (Ilex paraguariensis), a drink with high antioxidant capacity in the bone naturally perimenopausadas rats. Perimenopausadas Wistar rats were treated with MC at a dose of 20 mg / kg body mass (mc) for four weeks and compared with the untreated group. Group of adult rats was also investigated to confirm the effects of perimenopause. The activity of the enzyme tartrate resistant acid phosphatase (TRAP) and alkaline phosphatase (ALP) were investigated in plasma. Areal bone mineral density (aBMD) area occupied by adipocytes (AOA), number of osteocytes (N.Ot), trabecular bone volume (TBV) and immunohistochemistry for superoxide dismutase (SOD2), osteoprotegerin (OPG), TRAP and binder the receptor activator of the nuclear factor-kB (RANKL) were evaluated at the femoral neck. Lipid peroxidation (MDA) and SOD activity were determined in bone homogenates. Treatment with MT was able to attenuate the reduction of aBMD improve AOA N.Ot and TBV. These findings were followed by reduction of TRAP and ALP and plasma MDA and SOD2 in the bone. The MT minimizes oxidative stress and bone resorption, thereby attenuating the osteopenia of perimenopausal rats